Integrating the CER Framework in Argumentative Writing to Foster Logical Thinking and Evidence-Based Reasoning - Kholida Dj.S, Intan; Suryani, Irma; Abrar, Mukhlash (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study investigates integrating the Claim, Evidence, and Reasoning (CER) framework to enhance students' argumentative writing skills, a critical competency in 21st-century literacy, and employing a mixed-method approach that combines a qualitative descriptive analysis with a pre-experimental design. Data were rigorously collected through semi-structured interviews, direct field observations, and comprehensive writing assessments, including pretest and posttest evaluations. This study employed a mixed-methods approach with a pre-experimental one-group pretest-posttest design involving 30 eleventh-grade students at MAS Al Khairiyah in Jambi, for a total of 412 students, selected through purposive sampling. Quantitative data from performance tests and qualitative data from observations and interviews were analyzed simultaneously using the N-Gain test and an interactive analysis model to describe students' cognitive transformation in argumentative writing. The findings reveal a significant improvement in all argumentative components, with a